The Role of Green Competency Development in Enhancing Market Competitiveness among Employees in Ecotourism Industry: A Systematic Literature Review - Aziza, Pretty Failasufa; Ardiyansah, Ardiyansah; Pramitasari, Anisa; Permatasari, Mudiana; Rozikin, Imam; Setyadin, Yuris (Graduate School, Universitas Brawijaya, 2025)
This study aims to analyze the role of green competency development in enhancing market competitiveness among employees in the ecotourism industry. Green competencies have become increasingly important in the era of the green economy, particularly in the ecotourism sector, which heavily relies on environmental sustainability. Using a Systematic Literature Review (SLR) approach, this study reviews and synthesizes various relevant studies on green competency development, market competitiveness, employee behavior, and ecotourism. Data were obtained from scholarly journals and other publications published within the last decade, with search criteria encompassing topics related to green competencies and competitiveness in sustainability-focused sectors. The findings suggest that the development of employees' green competencies, including an understanding of environmentally friendly practices and sustainable skills, can positively contribute to a company's market competitiveness in the ecotourism industry. The results also reveal that green competencies enhance the company's value and reputation, thus attracting environmentally conscious consumers. This study suggests that ecotourism managers should prioritize green training programs to strengthen the company's competitiveness in an increasingly sustainability-oriented market.